The interior design of a UP Child Development Center classroom an analysis - Cortez, Rochelle Ortanez; Mayo, Adelaida Villaraza (1995.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Child Development Center, College of Home Economics, University of the Philippines Diliman; Classrooms -- Philippines